Prospective evaluation of quality of life in children treated in UKALL 2003 for acute lymphoblastic leukaemia: A cohort study. Issue 11 (5th May 2017) - Eiser, C.; Stride, C.B.; Vora, A.; Goulden, N.; Mitchell, C.; Buck, G.; Adams, M.; Jenney, M.E.M.; ,
Abstract: Background: Health‐related quality of life (HRQoL) from diagnosis until end of treatment for children with acute lymphoblastic leukaemia was investigated, examining effects of age, gender, risk‐stratified treatment regimen, and therapy intensity (one vs. two 'delayed intensifications' [DIs]). Method: In a multi‐centre prospective study, parents reported their child's generic and disease‐specific HRQoL and their own care‐giving burden at five time points. From 1, 428 eligible patients, 874 parents completed questionnaires at least once during treatment. Results: At each time point, generic HRQoL was significantly lower than equivalent norm scores for healthy children. HRQoL decreased significantly at the start of treatment, before recovering gradually (but remained below pre‐treatment levels). Parents reported that older children worried more about side effects and their appearance, but showed less procedural anxiety than younger children. Concern for appearance was greater among girls than boys. Compared to Regimen B (i.e. additional doxorubicin during induction and additional cyclophosphamide and cytarabine during consolidation chemotherapy), patients receiving Regimen A had fewer problems with pain and nausea. There were no statistically significant differences in HRQoL by number of DI blocks received. Interpretation: HRQoL is compromised at all stages of treatment, and is partly dependent on age. The findings increase understanding of the impact of therapy on children's HRQoL and parental care‐giving burden, and will contribute to the design of future trials.